Pemikiran Ekologis pada Petani Kopi dalam Kawasan Hutan Konservasi di Desa Tiwingan Baru Kabupaten Banjar - Larasati, Aaqilah; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2024)
The agroforestry model has ecological values, where it is practiced by farmers in Tiwingan Baru Village, Banjar Regency. This research used qualitative methods, and a phenomenological research design. The research subjects were coffee farmers in Tiwingan Baru Village. The research data were collected through observation, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model. The results showed that coffee farmers in Tiwingan Baru Village implemented agroforestry farming practices supported by ecological thinking, so as to maintain the sustainability of the forest ecosystem of Tiwingan Baru Village. The agroforestry model practiced by the community manifests the environmental ethics of ecofeminism, which prioritizes care and compassion for nature. In terms of the concept of sustainable development, the forest management practices are able to: 1) maintain forest cover and avoid agricultural commodities that are bad for the ecosystem, so that the threat of deforestation can be avoided; 2) become a stable source of income for the community because the coffee commodity cultivated is an important commodity and is sustainable to the next generation; and, 3) raise awareness of the importance of institutional formation that supports the socio-economic processes of the community. The model of forest management through coffee agroforestry implemented by the community in Tiwingan Baru Village needs to be protected and sustained through strategic policies and empowerment programs. Furthermore, it is important that the forest management model is replicated elsewhere as a model of equitable and sustainable forest management.